Laeverin/aminopeptidase Q induces indoleamine 2,3-dioxygenase-1 in human monocytes - Takuma Suzuki; Takashi Iizuka; Kyosuke Kagami; Takeo Matsumoto; Rena Yamazaki; Takiko Daikoku; Akihito Horie; Masanori Ono; Akira Hattori; Hiroshi Fujiwara (iScience, 2023)
Summary: Human extravillous trophoblast (EVT) invades the maternal endometrium and reconstructs uterine spiral arteries cooperatively with maternal immune cells. Although EVT has allogeneic paternal antigens, the maternal immune system does not reject it. Here, we found that laeverin (LVRN), an EVT-specific cell surface peptidase, interacts with monocytes to produce indoleamine 2,3-dioxygenase-1 (IDO1). LVRN-transfected Swan71 cells, a cytotrophoblast-derived cell line, and increased IDO1 expression in PBMC under cell-to-cell interacting conditions. Soluble recombinant LVRN (r-LVRN) interacted with CD14-positive monocytes and induced their IDO1 expression without the intervention of other immune cell populations. LVRN-induced IDO1 production was promoted in PMA-activated monocyte-like THP-1 cells. Furthermore, r-LVRN decreased the tryptophan level and increased the kynurenine/tryptophan ratio in the culture media of the PMA-treated THP-1 cells. These findings suggest that LVRN is one of the key molecules that mediate the interaction between EVT and monocytes/macrophages and creates an immunosuppressive environment at the maternal-fetal interface in the uterus.